Advances in global leadership. Volume 13 - Osland, Joyce S.; Mendenhall, Mark E.; Reiche, Sebastian; Szkudlarek, Betina (Emerald Publishing Limited, 2020)
Advances in Global Leadership brings together insights from leading scholars and practitioners and presents fresh ideas from promising newcomers to the field. With its unique focus on addressing global leadership and collaboration in times of crisis, this volume is both timely and relevant during the Covid-19 pandemic and beyond;This volume is split into two parts: Part 1 of the volume presents research papers that advance our conceptualization and understanding of the construct of global leadership and identify a wide range of future research topics. Part 2 takes an applied perspective, showcasing approaches and solutions to global leadership practice, development, and teaching. The editors' conclusion chapter aims to expand current thinking on global leadership and recommend future research directions to advance the field. Given its multidisciplinary focus, this book is a must-read for scholars from a diverse set of scholarly fields and practitioners with a diverse set of global leadership roles. The Advances in Global Leadership series, with its finger firmly on the pulse of this exciting field, is an indispensable compendium of knowledge on global leadership.